Seismic response of a mid-story-isolated structure considering soil–Structure interaction in sloping ground under three-dimensional earthquakes - Wan, Feng; Li, Cheng; Li, Hong; Liu, Dewen; Yao, Shunzhong; Lei, Min (Frontiers in Earth Science, 2023)
Mid-story isolated structure is a kind of structure developed from the base isolated structure. Mid-story isolated structures located in sloping ground have become one of the research hotspots in recent years. It is not accurate if ignoring the soil-structure-interaction (SSI) effect and multi-dimensional earthquakes. This paper established the model of the mid-story isolated structure considering SSI in sloping ground. The elastic-plastic time history analysis was carried out under the one-dimensional (1D), two-dimensional (2D) and three-dimensional (3D) earthquakes. Under 3D earthquakes, the traditional 2D isolated bearing has limited damping capacity. Therefore, two kinds of 3D isolated bearings are designed. Results show that the seismic response of the mid-story isolated structure considering SSI in sloping ground can be amplified compared with the mid-story isolated structure without considering SSI. The seismic response of the structure under 3D earthquakes is more significant than that under 2D earthquakes and 1D earthquakes. For the two kinds of 3D isolated bearings, the minimum reduction rate of tensile and compressive stress is about 46% compared with the traditional 2D isolated bearings. When the 3D isolated bearings are used, the stress of the soil foundation decreases, which is more conducive to the stability of the soil foundation.